Synthesis and characterization of a fluorescent probe for α-tocopherol suitable for fluorescence microscopy. Issue 12 (15th June 2016) - Ghelfi, Mikel; Ulatowski, Lynn; Manor, Danny; Atkinson, Jeffrey
Graphical abstract: Abstract: Previously prepared fluorescent derivatives of α-tocopherol have shown tremendous utility in both in vitro exploration of the mechanism of ligand transfer by the α-tocopherol transfer protein (α-TTP) and the intracellular transport of α-tocopherol in cells and tissues. We report here the synthesis of a 4, 4-difluoro-4-bora-3a, 4a-diaza-s-indacene (BODIPY) containing α-tocopherol analog having extended conjugation with an alkenyl thiophene group that extends the absorption and emission maxima to longer wavelengths ( λ ex  = 571 nm and λ em  = 583 nm). The final fluorophore thienyl-ene-BODIPY-α-tocopherol, 2, binds to recombinant human α-TTP with a K d  = 8.7 ± 1.1 nM and is a suitable probe for monitoring the secretion of α-tocopherol from cultured Mcf7#189 cells.